Chapter Assessment of trace metal contamination and phosphorus dynamic in sediments of Monastir Bay (Tunisia) - Ben Mefteh, Amina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Metallic Trace Elements were measured in the sediment, their concentrations highlighted a moderate pollution despite the human activities (urban-wastewater, harbour, textile industries). The phosphorus dynamic is controlled by environmental conditions, (i) oxic sediment with basic pH enhance the FeOOH formation then the phosphorus fixation on FeOOH or CaCO3 in sediment whatever the sediment lithology and (ii) anoxic and acidic sediment enhance the formation of ROP (Residual Organic Phosphorus) in correlation with the presence of aquatic plants (Posidonia meadow) in the sediment.